2021
DOI: 10.1371/journal.ppat.1009328
|View full text |Cite
|
Sign up to set email alerts
|

A high-affinity RBD-targeting nanobody improves fusion partner’s potency against SARS-CoV-2

Abstract: A key step to the SARS-CoV-2 infection is the attachment of its Spike receptor-binding domain (S RBD) to the host receptor ACE2. Considerable research has been devoted to the development of neutralizing antibodies, including llama-derived single-chain nanobodies, to target the receptor-binding motif (RBM) and to block ACE2-RBD binding. Simple and effective strategies to increase potency are desirable for such studies when antibodies are only modestly effective. Here, we identify and characterize a high-affinit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 63 publications
2
35
0
Order By: Relevance
“… 59 The computationally designed FFWF mutant has ninefold higher affinity than the wild-type for RBD, with the increased binding mainly attributed to the slower off-rate. The K D of 1.8 nM for the FFWF mutant is in line with SARS CoV-2 monoclonal antibodies 56 59 and other therapeutics such as nanobodies 60 63 that potently neutralize SARS CoV-2. Although FFWF did not bind as tightly as v2 or v2.4 designed mutants, these designs were constructed after multiple rounds of experimental mutagenesis.…”
Section: Resultssupporting
confidence: 59%
“… 59 The computationally designed FFWF mutant has ninefold higher affinity than the wild-type for RBD, with the increased binding mainly attributed to the slower off-rate. The K D of 1.8 nM for the FFWF mutant is in line with SARS CoV-2 monoclonal antibodies 56 59 and other therapeutics such as nanobodies 60 63 that potently neutralize SARS CoV-2. Although FFWF did not bind as tightly as v2 or v2.4 designed mutants, these designs were constructed after multiple rounds of experimental mutagenesis.…”
Section: Resultssupporting
confidence: 59%
“…They include monoclonal antibodies CB6 35 ( c ), CV30 36 ( d ), REGN10987 12 ( e ), REGN10933 12 ( f ), and the two sybodies SR4 ( g ) and MR17 ( h ) characterized in this study. i The MR3-RBD binding is compatible with SR31, which targets a non-RBM surface 37 . In c – h , the epitopes of the antibodies are highlighted in cyan except for SR4 and MR17, which are shown in Fig.…”
Section: Resultsmentioning
confidence: 93%
“…3a ). Third, we conducted cross-competition assays using ACE2 and structurally characterized antibodies, including four monoclonal antibodies (mAbs; CB6 35 , CV30 36 , REGN10987, and REGN10933 12 ), and three sybodies (SR4, MR17, and SR31 37 ). MR3 competed with ACE2 and all the RBM antibodies (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The authors showed in a subsequent report that their homotrimeric Nb21 (PiN-21) require low-dosage (0.2–0.6 mg/kg) to protected infected Syrian hamster [94] . Many other recent studies have demonstrated and confirmed the potential of linker-based bi-paratopic or multi-paratopic nanobodies for enhanced blocking and neutralization of SARS-CoV-2 variants [63] , [95] , [96] , [97] .…”
Section: Avidity-inspired Approaches For Effective Viral Blockingmentioning
confidence: 94%